Upacara “Puja Chautu” Dan “Yen Kung” Dalam Agama Buddha - Agung Suharyanto; Hadion Wijoyo; Adhi Wibowo (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2021)
This research will explain about Chinese ethnic in Medan in carrying out the process of the service delegation ceremony / chau tu and asap / yen kung. TsewangLhama who comes from India, In this activity, the participants will be invited to do Chau Tu puja, and Yen Kung. The ceremony was held for the first time the participants attended the worshiping of Amitaba Buddha and Buddha Kwang Ting So. The method used in this research is descriptive qualitative to obtain information about the meaning and function of the Chautu and Yen Kung ceremonies. The ceremony that is carried out is a ceremony for the bestowal of services, as a manifestation of love for ancestors, parents, and deceased families.